Current Situation and Development Trend of China’s Agricultural Machinery Distribution - T. Chen (Сельскохозяйственные машины и технологии, 2021)
In the year of 2021, the Chinese government allocated 19 billion RMB for agricultural machinery subsidy. The data that accurately describes the scale of China’s agricultural machinery market could be calculated by analyzing the national agricultural machinery purchase investment, the total value of the parts market and the replacement market could be inferred. Since the implementation of agricultural machinery purchase subsidies, China’s comprehensive mechanization rate of crop cultivation, planting and harvesting has increased rapidly. In 2019, the national comprehensive mechanization rate of crop cultivation, planting and harvesting exceeded 70 percent, and the production of the three major food crops of wheat, rice and corn was basically mechanized. This paper analyzes the scale of the complete machinery market, the market scale of key products in the Chinese agricultural machinery market, the basic situation of Chinese agricultural machinery distribution companies, the basic situation of the Chinese agricultural machinery purchasing groups, and the main gathering platforms of the Chinese agricultural machinery distribution market, explaining the current status of China’s agricultural machinery distribution, putting forward suggestions for the development of China’s agricultural machinery distribution market. There are major contradictions in the agricultural machinery market in China. The most important one is between supply and demand. In terms of crops, the level of comprehensive mechanization of wheat, rice and maize is relatively high, while the level of comprehensive mechanization of cash crops such as cotton oil, sugar and vegetable tea is relatively low; from a regional perspective, the level of mechanization in the northern plains is relatively high, and the level of mechanization in the hilly and mountainous areas of the south is relatively low; from an industrial point of view, the level of mechanization of planting industry is relatively high, while the level of mechanization of animal husbandry, fi shery and processing is low. Meanwhile, the contradiction between manufacturers and distributors, as well as the end-users is further intensifying. This article attempts to explain the effi ciency and benefi t of agriculture and the return on investment of agricultural machinery purchase. Only when agriculture is competitive, has good effi ciency and benefi ts, and the purchase of agricultural machinery has a good rate of return on investment, can the industry develop healthily.